Notes on an Ex White Man’s Form of Life Toward Social Death - Andrew Santana Kaplan (Black Theology Papers Project)
This paper considers John Brown as a paradigmatic respondent to James Cone’s and Frank Wilderson’s charges for Humanity to “become Black.” More precisely, this paper takes Du Bois’s reading of John Brown as a meditation upon what Nahum Chandler describes as the “soul of an ex White man.” For Du Bois, Brown’s taking up of the “Negro question” proceeded to shape his entire existence. By drawing on Giorgio Agamben’s messianic conception of “form of life” and Afropessimism’s elaboration of the “Negro question” through the paradigm of social death, this paper offers a reading of Du Bois’s Brown as a form of life toward social death